Osteoporosis and Alzheimer´s disease (or Alzheimer´s disease and Osteoporosis) - Wanionok, Nahuel Ezequiel (2024)
Alzheimer´s disease (AD) and osteoporosis are two diseases that mainly affect elderly people, with increases in the occurrence of cases due to a longer life expectancy. Several epidemiological studies have shown a reciprocal association between both diseases, finding an increase in incidence of osteoporosis in patients with AD, and a higher burden of AD in osteoporotic patients. This epidemiological relationship has motivated the search for molecules, genes, signaling pathways and mechanisms that are related to both pathologies. The mechanisms found in these studies can serve to improve treatments and establish better patient care protocols.